Impact of Renal Dysfunction on Liver Transplantation: a Retrospective Study in 708 Orthotopic Liver Transplant Recipients - Ferreira, AC (2010)
Renal dysfunction often complicates the course of orthotopic liver transplant recipients and is associated with increased morbid -mortality. The aims of this study were to determine the incidence of chronic renal disease and its impact on patient survival. Clinical data included age, gender and weight,aetiology of hepatic failure, presence of diabetes,hypertension, hepatitis B and C infection, renal dysfunction pretransplant and immunosuppression. Laboratory data included serum creatinine at days 1, 7, 21, month 6, 12 and yearly. The glomerular filtration rate was determined by Cockcroft-Gault equation. We studied retrospectively from September 1992 to March 2007 708 orthotopic liver transplant recipients. Mean age 44±12.6 years, 64% males, 17% diabetic, 18.8% hypertensive, 19.9% with hepatitis C and 3.8% hepatitis B. Renal dysfunction pretransplant was known in 21.6%. Mean follow-up was 3.6 years. Mean transplant survival 75% at 12 months. 154 patients died. Univariate and multivariate analyses were performed and a p<0.05 was considered significant. Acute kidney injury occurred in 33.2%. Chronic kidney disease stage 3 was observed in 34.3%,stage 4 in 6.2% and stage 5 in 5.1%. At the time of this study, 46.4% were on Cyclosporine A, 44.7% on tacrolimus and 8.9% on sirolimus. Using multivariate analysis, renal dysfunction was correlated with renal dysfunction pre -orthotopic liver transplant (p<0.001), acute kidney injury (p<0.001), haemodialysis development (p<0.001), and inversely correlated with the use of mycophenolate mophetil (p<0.001); mortality was positively correlated with renal dysfunction pretransplant (p=0.03),chronic kidney disease stage 4 (p=0.001), chronic kidney disease stage 5 (p<0.001) and inversely correlated with the use of tacrolimus (p=0.006). In conclusion orthotopic liver transplant recipients are disposed to renal complications that have a negative impact on survival of these patients.